Modele log-liniowe dla zmiennych porządkowych - Kasprzyk, Iwona (Log-Linear Models for Ordinal Variable, 2006)
The main purpose of this article is to show log-linear models for ordinal variables. The log-linear models examine the relationship between two or more categorical variables in a contingency table. This article shows the various types of log-linear models i.e. uniform association model, row effect model, column effect model and RC model proposed by Goodman in 1979.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 86-94